2019
DOI: 10.1161/jaha.119.012157
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Novel Risk Score for In‐Hospital Major Bleeding in Acute Myocardial Infarction:—The SWEDEHEART Score

Abstract: Background Bleeding risk stratification in acute coronary syndrome is of highest clinical interest but current risk scores have limitations. We sought to develop and validate a new in‐hospital bleeding risk score for patients with acute myocardial infarction. Methods and Results From the nationwide SWEDEHEART (Swedish Web‐System for Enhancement and Development of Evidence‐Based Care in Heart Disease Evaluated According to Recommended Therapies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 43 publications
2
27
2
Order By: Relevance
“…Previous studies demonstrated that the prevalence of history of bleeding increased the risk of bleeding events. 24 25 26 In the previous all-comers study, the prevalence of history of bleeding was approximately 6%, 26 whereas in the present study, a prevalence of only 0.6% was observed. This is a hypothesis-generated study using a database of a randomized controlled trial and bleeding events were site-reported.…”
Section: Discussioncontrasting
confidence: 70%
“…Previous studies demonstrated that the prevalence of history of bleeding increased the risk of bleeding events. 24 25 26 In the previous all-comers study, the prevalence of history of bleeding was approximately 6%, 26 whereas in the present study, a prevalence of only 0.6% was observed. This is a hypothesis-generated study using a database of a randomized controlled trial and bleeding events were site-reported.…”
Section: Discussioncontrasting
confidence: 70%
“…Previous studies constructed nomograms for AMI, but these nomograms only focused on the short-term mortality of patients and the occurrence of complications, such as bleeding and acute kidney injury. 22,23 To the best of our knowledge, this study was the first to establish a nomogram for predicting the long-term survival of patients with AMI. In our prediction model, the predictors integrated into the model were easy to obtain and calculate, including vital signs, such as RR, and routine laboratory tests, such as BUN.…”
Section: Discussionmentioning
confidence: 96%
“…This was also a form of internal validation because their cohorts were randomly created [ 9 ]. Moa Simonsson et al [ 6 ] used 97,597 patients to develop a model to predict in-hospital major bleeding in acute myocardial infarction. The internal and temporal validity of the model were assessed; the temporal validity of the score was assessed using internal-external cross-validation [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alexander et al [ 9 ] developed a model to predict in-hospital major bleeding in acute myocardial infarction, but their models were only internally validated. Moa Simonsson et al [ 6 ] developed a model to predict in-hospital major bleeding in acute myocardial infarction, and the internal and temporal validity of the model was assessed. The aim of our study was to develop and externally validate a diagnostic model of in-hospital bleeding in patients with acute STEMI.…”
Section: Introductionmentioning
confidence: 99%